Mass mortality of fingerlings of Labeo rohita (Hamilton) in a nursery pond - Sugumar, G; Karunasagar, Indrani; Karunasagar, Iddya (Indian Journal of Fisheries, 2011)
The cause of large scale mortality in fingerlings of Labeo rohita (Hamilton)stocked in a nursery pond was investigated. Examination of gills of healthylooking fingerlings revealed heavy infestations of Dactylogyrus. Bacteriologicalstudies showed presence of Aeromonas hydrophila, A.sobria, Vibrio Spp.and enterobacteriaceae in the internal organs of infected fingerlings. Dip treatmentof fingerlings in formalin solution (50 ppm) controlled the mortality. Mortalityceased after one week of treatment . Examination of healthy fish at thisstage showed absence of Dactylogyrus on the gills and bacteria in the internalorgans. Presence of different types of bacteria in Dactylogyrus infected fish suggeststhat bacteria might have gained entry into the internal organs throughdamaged gills